Validity of predictive equations for 24-h urinary potassium excretion based on timing of spot urine collection among adults: the MESA and CARDIA Urinary Sodium Study and NHANES Urinary Sodium Calibration Study. Issue 3 (11th September 2018) - Mercado, Carla I; Cogswell, Mary E; Loria, Catherine M; Liu, Kiang; Allen, Norrina; Gillespie, Cathleen; Wang, Chia-Yih; de Boer, Ian H; Wright, Jacqueline
ABSTRACT: Background: 24-h urine collections are the suggested method to measure daily urinary potassium excretion (uK) but are costly and burdensome to implement. Objective: This study tested how well existing equations with the use of spot urine samples can estimate 24-h uK and if accuracy varies by timing of spot urine collection, age, race, or sex. Design: This cross-sectional study used data from 407 participants aged 18–39 y from the Washington, DC area in 2011 and 554 participants aged 45–79 y from Chicago in 2013. Spot urine samples were collected in individual containers for 24 h, and 1 for each timed period (morning, afternoon, evening, and overnight) was selected. For each selected timed spot urine, 24-h uK was predicted through the use of published equations. Difference (bias) between predicted and measured 24-h uK was calculated for each timed period and within age, race, and sex subgroups. Individual-level differences were assessed through the use of Bland-Altman plots and correlation tests. Results: For all equations, regardless of the timing of spot urine, mean bias was usually significantly different than 0. No one prediction equation was unbiased across all sex, race, and age subgroups. With the use of the Kawasaki and Tanaka equations, 24-h uK was overestimated at low levels and underestimated at high levels, whereas observed differential bias with the Mage equation was in the opposite direction. Depending on prediction equation and timing of urine sample, 61–75% of individual 24-h uKs were misclassified among 500-mg incremental categories from <1500 to ≥3000 mg. Correlations between predicted and measured 24-h uK were poor to moderate (0.19–0.71). Conclusion: Because predicted 24-h uK accuracy varies by timing of spot urine collection, published prediction equations, and within age-race-sex subgroups, study results making use of predicted 24-h uK in association with health outcomes should be interpreted with caution. It is possible that a more accurate prediction equation can be developed leading to different results.